Schizophrenia spectrum disorders in India: A population-based study - Prakyath Ravindranath Hegde; Lakshmi P. Nirisha; Chethan Basavarajappa; Satish Suhas; Channaveerachari Naveen Kumar; Vivek Benegal; Girish N. Rao; Mathew Varghese; Gopalkrishna Gururaj; NMHS National Collaborators Group (Indian Journal of Psychiatry)
Introduction: Schizophrenia spectrum disorders represent a significant global health concern, contributing significantly to the global burden of disease. The National Mental Health Survey (NMHS) of India, conducted between 2015 and 2016, investigated the prevalence and epidemiological correlates of schizophrenia spectrum disorders in India. Materials and Methods: The NMHS conducted a population-based cross-sectional study in 12 Indian states from 2015 to 2016, encompassing 34,802 adults. The overall study design of the NMHS was a multistage, stratified, random cluster sampling technique, incorporating random selection based on probability proportion to size at each stage. The Mini-International Neuropsychiatric Interview 6.0 was used for psychiatric diagnoses, disability was assessed using Sheehan's disability scale, and the illness-related socioeconomic impact was assessed using a questionnaire based on the World Health Organization Disability Assessment Schedule 2.0. Firth penalized logistic regression was employed to understand the correlates of current schizophrenia spectrum disorder. Results: The study found a lifetime prevalence of schizophrenia spectrum disorders at 1.41%, with a current prevalence of 0.42%. A substantial treatment gap of 72% existed for current cases, rising to 83.3% in urban non-metro areas. The penalized logistic regression revealed that the age group category of 30–49 years, unemployed status, and lower education level had higher odds of association with schizophrenia spectrum disorders. Conclusion: The primary finding of this study is a lifetime prevalence of 1.41%, a current prevalence of 0.42%, and a substantial treatment gap of 72%. Addressing this treatment gap and holistic intervention is crucial for reducing the socioeconomic impact of this disorder. Strengthening the National Mental Health Program and implementing community-based rehabilitation are essential first steps in this direction.